Rapid visual detection of anisakid nematodes using recombinase polymerase amplification and SYBR Green I - Chen, Xiuqin; Zhao, Lianjing; Wang, Jiahui; Wang, Haolu; Qiu, Yangyuan; Dong, Zijian; Zhang, Chunling; Liu, Mingyuan; Wang, Xuelin; Bai, Xue (Frontiers in Microbiology, 2022)
Anisakidosis is a food-borne parasitic disease (FBPD) caused by the third-stage larvae of the family Anisakidae. Therefore, it is important to develop a simple, rapid and equipment-free detection method for anisakids in fish samples or seafood since current methods are time-consuming and require complex instruments. In this study, a recombinase polymerase amplification (RPA)-based method was established for the first time to detect anisakids by targeting the internal transcribed spacer (ITS) regions. The detection results were visualized by including SYBR Green I (SG) in the method. The sensitivity of RPA-SG assay was 102 copies per reaction of recombinant plasmid (within 20 min at 37 °C), similar to quantitative real-time PCR (qPCR). The assay had high specificity for detecting anisakids against other related parasites and host fish. In addition, the assay was further used to detect fresh marine fish contaminated with anisakids and it showed high precision. These results indicate that the novel RPA-SG assay suitable for visual detection of anisakids in the field and food safety control.